P204 The Burden of repeated asthma admissions and associations with psychiatric comorbidity. (2nd December 2011) - Burke, H; Pond, Z; Duffus, C; Kurukulaaratchy, R J
Abstract : Rationale and Objectives: While only 10% of asthmatics have "Difficult Asthma" they account for 80% of asthma-related expenditure. Aggravating comorbidities are common in patients with Difficult Asthma including Psychiatric disorders, such as major depression, which is present in 29%.1 We sought to characterise the annual burden of repeated asthma admissions to our Hospital and assess the influence of psychiatric comorbidity on this group with Difficult Asthma. Methods: We systematically searched the hospital database for patients who had been acutely admitted on two or more occasions in 2010 for asthma at Southampton General Hospital (Southampton, UK). Data were collected retrospectively and covered patient demographics, admission details, asthma severity, physical and psychiatric co-morbidity. Coding data for each admission was analysed to determine admission costs. Data were analysed using SPSS (V.19.0) to determine significant characteristics of this Difficult Asthma group and to assess the influence of psychiatric comorbidity on those parameters. Results: There were 396 admissions for acute asthma in 2010, involving 305 patients. Of these, 36 (11.8%) patients were admitted on =2 occasions, accounting for 32.1% of admissions. Repeated admission patients consumed 895 bed-days and were predominantly female (72.2%; p=0.012). They commonly had aggravating comorbidities, the most predominant being diagnosed psychiatric disease (69.4%; p=0.03). Those patients with psychiatric comorbidity showed significantly higher Body Mass Index (p=0.012), plus greater prevalence of obesity (p=0.05) and dysfunctional breathing (p=0.012) than patients without psychiatric comorbidity. They also showed trends for higher prevalence of other aggravating comorbidity like Gastro-Oesophageal Reflux Disease (p=0.07) and for greater median bed-days/length of stay. The annual cost for repeated asthma admission was £226 536 of which patients with psychiatric comorbidity consumed £164 660 (72.7% of costs). Conclusions: A significant proportion of patients with repeated asthma admission have psychiatric comorbidity. When present in such patients, psychiatric comorbidity is associated with obesity and dysfunctional breathing. Patients with Difficult Asthma and psychiatric comorbidity pose a significant burden on Secondary Healthcare resources. Optimal asthma care could benefit from targeting support and treatment for underlying psychiatric illness.